Fam102a translocates Runx2 and Rbpjl to facilitate Osterix expression and bone formation - Yu Yamashita; Mikihito Hayashi; Anhao Liu; Fumiyuki Sasaki; Yosuke Tsuchiya; Hiroshi Takayanagi; Mitsuru Saito; Tomoki Nakashima (Nature Communications)
Abstract Bone remodeling maintains the robustness of the bone tissue by balancing bone resorption by osteoclasts and bone formation by osteoblasts. Although these cells together play a crucial role in bone remodeling, only a few reports are available on the common factors involved in the differentiation of the two types of cells. Here, we show family with sequence similarity 102 member A (Fam102a) as a bone-remodeling factor that positively regulates both osteoclast and osteoblast differentiation. Fam102a regulates osteoblast differentiation by controlling recombination signal binding protein for immunoglobulin κ J region-like (Rbpjl). The Fam102a-Rbpjl axis promotes the nuclear translocation of transcription factors and enhances the expression of Osterix, a transcription factor essential for osteoblast differentiation. The deletion of Fam102a or a functional mutation in Rbpjl leads to osteopenia accompanied by reduced osteoblastic bone formation. Thus, the Fam102a-Rbpjl axis plays an important role in osteoblasts and this finding provides insights into bone remodeling.